Otimização da densidade de empacotamento de agregado seco utilizado na produção de pasta anódica para a indústria do alumínio - Vry, Beatriz Furquim (2013)
The aluminum industry requires, among other materials, coal tar pitch and calcined petroleum coke for the production of carbon anodes that provides the electrolytic reduction of aluminum oxide. The production of this composite requires specific processing in order to give characteristics such as low electrical resistivity, high density and higher air and carbon dioxide reactivity residue, as well as a suitable format for its manipulation through specific vehicles. In recent years, both inputs have undergone significant qualitative degradation and increased costs, forcing industries to seek for non-traditional suppliers, and also required from the production process of anodic folder a significant increase in the quality of the product during processing. The development of new products from raw materials of low quality or non-traditional requires study and experimentation, so that they can be used industrially. Thus, this project involved the study and optimization of different particle size formulations of petroleum coke in the dry aggregate, area still slightly dominated in the productive sector of the Aluminum, using the theoretical models of packaging Andreasen and Alfred. The formulations developed in this study were compared to the formulation originally used by an industry through measures flowability and apparent baked density. The results have shown that both the equations of Alfred and Andreasen, for distribution coefficient 0.37 and 0.52 respectively, can be applied to the Aluminum Industry resulting into products significantly different from the point of view of quality.